“A / music / at rest”: Late Duncan and Objectivist Poetics - Jeffrey Twitchell-Waas (Sillages Critiques)
Throughout Robert Duncan’s poetic life, Louis Zukofsky represented an important challenge, an admired mentor who in so many respects espoused modernist principles directly opposed to Duncan’s own self-proclaimed “romantic” propensities. However, it is in the late Ground Work period that Duncan takes Zukofsky as something more than a disciplined mentor and attempts to internalize Zukofsky as a troubling but generative presence in his work. This article offers both close readings of specific poems alongside broader comparative discussion of their respective poetic principles to highlight the significance of Zukofsky in Duncan’s late poetry as a critically antagonistic counter to Duncan’s more self-indulgent expansiveness, as well as offering a model for a looser conception of the long poem that defines itself in process rather than driven by the arguments or mythopoetic structures that Duncan found so seductive even while resisting them.